Hubungan Asupan Makan dengan Kejadian Kurang Energi Kronis (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Sukaraja Kota Bandar Lampung - Ahmad Alvin Dictara; Dian Isti Angraini; Diana Mayasari; Aila Karyus (MAJORITY, 2020)
The prevalence of chronic energy deficiency (CED) in Lampung Province in 2013 was 21,3% for pregnant women and 17,5% in non-pregnant women, in Bandar Lampung was 24,5%. The problem of chronic energy deficiency (CED) in women is influenced by various factors, namely food intake, incorrect understanding of nutrition, the entry of undernourished food products from outside and chronic infectious diseases.This study was conducted to determine the relation of food intake with CED in pregnant women in working area of Sukaraja health center in Bandar Lampung.This type of researchwas quantitative using cross sectional approach with consecutive sampling technique. The inclusion criteria were pregnant women in the first and second trimesters, aged 20-35 years, and willing to be respondents. The exclusion criteria were women with chronic infection, anemia, and hyperemesis gravidarum. The research respondents were 71 pregnant women. Food intake data were obtained from the Semi quantitative food frequency questionnaire and CED data by measuring the upper arm circumference (LILA). Data were analyzed by fisher exact test.The results showed that there were 8.5% of respondents suffering from CED. Respondents who have less energy intake (36.6%), less carbohydrate intake (69.0%), less protein intake (11.3%), and less fat intake (39.4%). Based on the results of the analysis, it was found that energy and protein intake was associated with CED (p = 0.022) and (p = 0.017), while carbohydrate and fat intake was not related to CED (p = 0.167) and (p = 0.204). The conclusion of this study is that there is a significant relationship between energy and protein intake with the incidence of CED in pregnant women in the work area of Sukaraja Health Center, Bandar Lampung City.